Ideology of Place: A reading of the short story collection (And Ask Them About the Village) by the short story writer Anmar Rahmatullah - Abdul Karim, Duaa (Al-Adab Journal, 2025)
Ideology is an attempt to dig beneath the surface of the apparent meaning towards the deeper meanings, and a reactionary analysis of the ideas and visions presented by the text, and seeks to oppose their course and immanent to their true origins. This research is a reading of selected examples from the short story collection (And Ask Them About the Village) by the Iraqi storyteller (Anmar Rahmatullah). Issued by Dar Sutour for the year (2016), which reshaped reality in a fantasy style that discusses the problems of the place in a way of encryption and concealment. The choice was based on the stories in which the place was clear and explicit in the naming, which is the village as a written representation of the world that seemed characterized by dystopia at times and barbarism and backwardness at other times. , with the issues and crises it produces that are closely related to man and the social system, as it derives its entity from an important theme related to the fragmented relationship between the individual and authority in the system that is driven by hybrid ideologies and awareness methods that belong to the life of the jungle, so the stories move on a woven ground in an exotic symbolic style that is effective in forming vision and openness. Interpretation by employing intellectual shifts and stylistic paradox in addressing the dilapidated reality in which man finds himself surrounded by walls of alienation and absurdity. The researcher intended to read the place from an ideological point of view, while theorizing the term critically and revealing the nature of ideology and its relationship to literature, then moving on to the stories and trying to analyze the place. In it, with its multiple formats, including revolutionary, humanitarian, and others.